INTEGRATIVE LEARNING MODEL TYPE A SEQUENCED IN LEARNING WRITING IN CLASS VII STUDENTS OF UPTD SMP NEGERI 34 SINJAI - Risal, Syamsul (Publikasi dan UKI Press UKI Toraja., 2022)
The aim of this research is to identify the effectiveness of the sequenced type integrative learning model in learning to write for class VII students at UPTD SMP Negeri 34 Sinjai. The researcher was applied pre-experimental design the population is the second-grade students of UPTD SMP Negeri 34 Sinjai in academic year 2021/2022. In analyzing the numerical data, the writer was used SPSS for windows. Basically, all learning models that are implemented are designed in the learning process, if they are implemented with a full sense of responsibility, the results achieved can be meaningful for students and teachers as well as all existing components, including the government and society in general. The improvement in students' writing skills in research can be seen from the increase in the number of words in each sentence produced when students write. The data from this research indicates that the application of integrated learning with a sequenced model through deep thinking skills strategies can increase children's vocabulary and understanding of good behavior related to peaceful values.